2020
DOI: 10.3390/ijms21228491
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of miR-9-5p, miR-124-3p, miR-21-5p, miR-138-5p, and miR-1-3p in Glioblastoma Cell Lines and Extracellular Vesicles

Abstract: Glioblastoma (GBM), the most common primary brain tumor, is a complex and extremely aggressive disease. Despite recent advances in molecular biology, there is a lack of biomarkers, which would improve GBM’s diagnosis, prognosis, and therapy. Here, we analyzed by qPCR the expression levels of a set of miRNAs in GBM and lower-grade glioma human tissue samples and performed a survival analysis in silico. We then determined the expression of same miRNAs and their selected target mRNAs in small extracellular vesicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 75 publications
(123 reference statements)
0
27
0
Order By: Relevance
“…MiR-21 is a well-studied miRNA, which acts as an oncomir and associates with a malignant phenotype [ 4 , 49 ]. It has been very recently reported being significantly downregulated in GBM CSCs compared to astrocytes [ 11 ] and has already been shown to associate with a more differentiated phenotype [ 50 , 51 ]. The primary CSCs utilized in the present manuscript have been assessed molecularly and resulted to belong mostly to the proneural transcriptional subgroup [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MiR-21 is a well-studied miRNA, which acts as an oncomir and associates with a malignant phenotype [ 4 , 49 ]. It has been very recently reported being significantly downregulated in GBM CSCs compared to astrocytes [ 11 ] and has already been shown to associate with a more differentiated phenotype [ 50 , 51 ]. The primary CSCs utilized in the present manuscript have been assessed molecularly and resulted to belong mostly to the proneural transcriptional subgroup [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…GBM prognosis is generally poor and the median survival is only 14 months, while the 5-year survival rate is unfortunately between 5%–10% [ 7 , 8 , 9 , 10 ]. Overall, 90% of GBM originate de novo while the remaining 10% arise from lower-grade glioma [ 11 , 12 ]. Although the exact etiology of GBM is still being explored, it has been reported that ionizing radiation at high-dose and rare genetic disorders could facilitate the onset of GBM [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-21 represents a key regulator of the EMT signaling that has been shown to be one of the earlier players in CSC/CIC formation [ 203 ]. MiR-21 has also been reported in another study to be down-regulated in GBM CSCs/CICs as compared to astrocytes [ 204 ] and shown to be associated with a differentiated phenotype in GBM [ 205 , 247 ].…”
Section: The Dual Role Of Micrornas In Orchestrating Pro-tumoral Amentioning
confidence: 95%
“…miRNAs are short sequence single-stranded RNAs with a major role in gene regulation (19). Several in vitro studies using microarray have shown the involvement of miRNAs (including miR-21, mir-29 miR-210, miR-148, and many others) in enhancing proliferation and inhibiting tumor cell apoptosis in GBM (20)(21)(22)(23)(24)(25). mir-21 has been mostly studied as a major GBM cell regulator (26) and has also been shown to be transferred in the cargo of GBM EVs (27).…”
Section: Role Of Evs In Glioma What Can They Do?mentioning
confidence: 99%